2002
DOI: 10.1053/rmed.2002.1307
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of asthma patients with herbal medicine TJ-96: a randomized controlled trial

Abstract: Alternative medicine use has increased at a remarkable pace all over the world in recent years. Although herbal medicine for the treatment of asthma is becoming the focus of public attention, randomized studies had not been performed, even in Eastern countries including Japan. This study was designed to investigate whether one of the Japanese government approved herbal complexes Saiboku-to (TJ-96) is effective for the treatment of atopic asthma, and to investigate whether this protective activity is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 23 publications
0
48
0
Order By: Relevance
“…In the present study we observed that oral administration of decoction was more used for the treatment of asthma. The oral administration of Japanese herbal complex Saiboku-to (TJ-96) significantly decrease asthma symptoms, blood eosinophils and serum eosinophilic cationic protein (Urata et al, 2002). In addition, herb decoction could improve airway hyper-responsiveness in stabilized asthmatic children (Chan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study we observed that oral administration of decoction was more used for the treatment of asthma. The oral administration of Japanese herbal complex Saiboku-to (TJ-96) significantly decrease asthma symptoms, blood eosinophils and serum eosinophilic cationic protein (Urata et al, 2002). In addition, herb decoction could improve airway hyper-responsiveness in stabilized asthmatic children (Chan et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Herbal preparations have been cited as the third most popular complementary treatment modality by British asthma sufferers (Huntley and Ernst, 2000;Urata et al, 2002). Consequently, in the recent decades, the medicinal plants used in the management of the disease have attracted the attention of some authors, through the screening for immunomodulatory activity of plant extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Reporting of sample size calculation Of the 361 search results, 20 studies fulfilled the inclusion criteria [9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. 11 of the 20 (55%) did not report how the sample size was calculated.…”
Section: Resultsmentioning
confidence: 99%
“…One double blind placebo controlled study performed in asthma subjects showed that the gum resin of Boswellia serrata (used in Ayurvedic remedies) was able to significantly improve symptoms and FEV1 after a 6-week course [48]. Two studies reported that saiboku-to (TJ96) improved asthma symptoms, exerted a steroid-sparing effect, reduced bronchial responsiveness and decreased sputum eosinophils in asthma patients [49,50]. One controlled study in 8 asthmatics showed that an extract from Ginko biloba protected against bronchial specific challenge [51].…”
Section: Phytotherapymentioning
confidence: 99%